Real Time Vehicle Monitoring and Record Fetching System from Server to Traffic Police’s Smart Phone - K. Sasikanth Reddy, Komala R., (Design Engineering, 2021)
As demand grows, the number of automobiles on the road grows at a rapid pace. As a result, maintaining the details of the cars is critical for a country's administration. Information such as ownership, insurance, emissions, and road tax must be kept up to date and accessed quickly and readily. Even for crime purpose the vehicles are used. So, depending on the demand of the requirements we have proposed this model for real time vehicle’s monitoring and Record Fetching System. We have proposed a secured server for keeping the vehicle’s records. The vehicle’s ownership information will be uploaded by the RTO to the server. The insurance companies need to upload the vehicle’s insurance details to the server. Same task has to be done by the authorized emission centres. In the road signal cameras will be deployed. The transmitters at the road signal capture the image of number plate of the vehicle and transmit the image to the server along with the road signal code. In the server the image is processed and the details of the vehicle are fetched. If it finds any expired data then it calculates the current location of the vehicle based on the road signal code. Based on the calculated location the server sends the alert message to the nearby traffic police’s smart phone. Even if the traffic police want to check the details of any vehicle’s it takes the image of the number plate from the smart phone and the image will be send to the server and the server sends the information to the phone.